1966
DOI: 10.1136/bmj.2.5509.342
|View full text |Cite
|
Sign up to set email alerts
|

Mefenamic acid and flufenamic acid compared with aspirin and phenylbutazone in rheumatoid arthritis.

Abstract: The only advantage of the Davis pipette is that patients can take their own sample without the need to attend a clinic or to see a doctor; it might therefore be possible to reach a larger proportion of the population at risk. However, the low rate of detection would necessitate repeated screenings of each patient at fairly short time-intervals, and although the initial response might be good, it could prove difficult to persuade women to take repeated samples, especially in view of the complaints from the clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

1967
1967
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(8 citation statements)
references
References 1 publication
0
8
0
Order By: Relevance
“…In clinical. trials Cahill, Hill, Jessop, and Kendall (1965), Barnardo, Currey, Mason, Fox, and Weatherall (1966), and Myles, Bacon, and Williams (1967) have suggested that it is of comparable value to aspirin and phenylbutazone, but has a very low incidence of upper intestinal side-effects, which are common with the majority of drugs used in chronic rheumatic diseases. In view of the pogsible relation between mefenamic acid and haemolytic anaemia long-term therapy with this drug should be undertaken with caution and the patients should be watched carefully for evidence of haemolysis.…”
Section: Discussionmentioning
confidence: 99%
“…In clinical. trials Cahill, Hill, Jessop, and Kendall (1965), Barnardo, Currey, Mason, Fox, and Weatherall (1966), and Myles, Bacon, and Williams (1967) have suggested that it is of comparable value to aspirin and phenylbutazone, but has a very low incidence of upper intestinal side-effects, which are common with the majority of drugs used in chronic rheumatic diseases. In view of the pogsible relation between mefenamic acid and haemolytic anaemia long-term therapy with this drug should be undertaken with caution and the patients should be watched carefully for evidence of haemolysis.…”
Section: Discussionmentioning
confidence: 99%
“…Barnardo, Currey, Mason, Fox, and Weatherall (1966) showed that mefenamic acid was a comparable analgesic to aspirin and phenylbutazone. Young (1963) showed that mefenamic acid was comparable to oxyphenbutazone.…”
Section: Discussionmentioning
confidence: 99%
“…Five patients had side-effects with both mefenamic Discussion The preliminary assessment indicated that mefenamic acid was a superior analgesic to indomethacin and showed fewer side-effects. Barnardo, Currey, Mason, Fox, and Weatherall (1966) showed that mefenamic acid was a comparable analgesic to aspirin and phenylbutazone. Young (1963) showed that mefenamic acid was comparable to oxyphenbutazone.…”
Section: Investigationsmentioning
confidence: 99%
“…Prednisone proved more effective in reducing the number of joints involved and in increasing the strength of grip; it also markedly reduced the average ESR whereas flufenamic acid did not influence this measurement. Barnardo, Currey, Mason, Fox, and Weatherall (1966) compared mefenamic acid and flufenamic acid with aspirin and phenylbutazone in female outpatients with rheumatoid arthritis; phenylbutazone was preferred slightly but not significantly more often than any other drug and flufenamic acid was least popular, but again not significantly. The design of this trial provided for adjustment of dosage to the need of individual patients and equipotent daily doses of the trial drugs were estimated as 2 -4 g. for aspirin, 0 * 33 g. for phenylbutazone, 1 * 7 g. for mefenamic acid, and 0-67 g. for flufenamic acid.…”
mentioning
confidence: 98%